Investigation on three-body abrasive wear of ferritic steels, austenitic steel, and low-carbon steel - Wesley S.B.; Goyal H.S.; Harsha A.P. (My University, 2025)
In order to minimize the investment costs, the use of ferritic stainless steels is being explored for various processing industries. International Stainless Steel Forum suggested the use of ferritic steels AISI 439 and 444 in cane sugar industry instead of austenitic steels and lowcarbon steels. The objective of this investigation is to evaluate the abrasion resistance of these ferritic grades and to compare and rank them against austenitic steel AISI 304 and low-carbon steel SAE 1010 for use as construction material in sugar mills. Optical microscope, microhardness tester, and scanning electron microscope have been used to characterize the abraded specimens. The abrasion resistances AISI 439 and 444 grade steels are found to be moderately better than those of the other two materials in the abrasion test. © 2011 Authors.